Sea-ice Melting, Collective Inuit Peoples’ Rights and the Human Rights Discourse: A Critical Legal Analysis of the Nunavut Governance System - Le Teno, Sandrine; Frison, Christine (Environmental Policy and Law, 2021)
Climate change has increasing visible effects on the environment, particularly in the Arctic, where the sea-ice melted faster in 2020 than any time before. It directly threatens the Inuit people’s survival, whose livelihood is mainly based on traditional modes of subsistence (hunting, fishing and gathering). In light of the environmental crisis, this paper carries out a critical analysis of the Nunavut (Canada) legal framework, granting Inuit specific rights regarding their traditional way of life. While recognizing that this framework implements international human rights legal standards, we argue that the human right lens presents limitations in addressing climate change impacts on Inuit livelihood. By acknowledging the developments following the adoption of the United Nations Declarations on the Rights of Indigenous Peoples and on the Rights of Peasants and Other Peoples Living in Rural Areas, leading to the recognition of some collective rights to communities and people living of the land, we address the gaps of human rights –which are mainly individual –to reflect the importance of recognizing collective rights in the adaptation to the global climate change challenge. Indeed, the paper argues for the necessity to recognize the community level in the climate international governance scene.